Selection of metal hydrides-based thermal energy storage: Energy storage efficiency and density targets. (13th December 2018) - Nyamsi, Serge Nyallang; Lototskyy, Mykhaylo; Tolj, Ivan
Abstract: Thermo-chemical energy storage based on metal hydrides has gained tremendous interest in solar heat storage applications such as concentrated solar power systems (CSP) and parabolic troughs. In such systems, two metal hydride beds are connected and operating in an alternative way as energy storage or hydrogen storage. However, the selection of metal hydrides is essential for a smooth operation of these CSP systems in terms of energy storage efficiency and density. In this study, thermal energy storage systems using metal hydrides are modeled and analyzed in detail using first law of thermodynamics. For these purpose, four conventional metal hydrides are selected namely LaNi5, Mg, Mg2 Ni and Mg2 FeH6 . The comparison of performance is made in terms of volumetric energy storage and energy storage efficiency. The effects of operating conditions (temperature, hydrogen pressure and heat transfer fluid mass flow rates) and reactor design on the aforementioned performance metrics are studied and discussed in detail. The preliminary results showed that Mg-based hydrides store energy ranging from 1.3 to 2.4 GJ m −3 while the energy storage can be as low as 30% due to their slow intrinsic kinetics. On the other hand, coupling Mg-based hydrides with LaNi5 allow us to recover heat at a useful temperature above 330 K with low energy density ca.500 MJ m −3 provided suitable operating conditions are selected. The results of this study will be helpful to screen out all potentially viable hydrides materials for heat storage applications. Highlights: A selection model for metal hydrides based heat storage systems was established. Two-Dimensional numerical model for estimating the energy storage efficiency and density was performed. The energy storage density depends solely on the materials intrinsic properties and the geometry of the reactor. The energy storage efficiency of high temperature metal hydrides pairs is around 70%.